Activation of the PI3K/Akt/mTOR and MAP kinase Signaling Pathways in Response to Acute Solar Simulated Light Exposure of Human Skin - Bermudez, Yira (Cancer Prev Res (Phila), 2015)
The incidence of skin cancer is higher than all other cancers and continues to increase, with an average annual cost over $8B in the United States. As a result, identifying molecular pathway alterations that occur with UV exposure to strategize more effective preventive and therapeutic approaches is essential. To that end, we evaluated phosphorylation of proteins within the PI3K/Akt and MAPK pathways by immunohistochemistry in sun-protected skin after acute doses of physiologically relevant solar simulated ultraviolet light (SSL) in 24 volunteers. Biopsies were performed at baseline, 5-minute, 1-, 5-, and 24-hour post SSL. Within the PI3K/Akt pathway, we found activation of Akt (Serine473) to be significantly increased at 5 hrs while mTOR (Serine2448) was strongly activated early and was sustained over 24-hour post SSL. Downstream we observed a marked and sustained increase in phospho-S6 (Serine235/S236) whereas phospho-4E-BP1 (Threonines37/46) was increased only at 24 hours. Within the MAPK pathway, SSL-induced expression of phospho-p38 (Threonine180/Tyrosine182) peaked at 1–5 hrs. ERK 1/2 was observed to be immediate and sustained post-SSL. Phosphorylation of histone H3 (Serine10), a core structural protein of the nucleosome, peaked at 5-hour post SSL. The expression of both p53 and COX-2 was increased at 5-hour and was maximal at 24-hour post SSL. Apoptosis was significantly increased at 24 hrs as expected and indicative of a sunburn-type response to SSL. Understanding the timing of key protein expression changes in response to SSL will aid in development of mechanistic-based approaches for the prevention and control of skin cancers.